2021
DOI: 10.7554/elife.64145
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional biofilm colony growth supports a mutualism involving matrix and nutrient sharing

Abstract: Life in a three-dimensional biofilm is typical for many bacteria, yet little is known about how strains interact in this context. Here, we created essential-gene CRISPRi knockdown libraries in biofilm-forming Bacillus subtilis and measured competitive fitness during colony co-culture with wild type. Partial knockdown of some translation-related genes reduced growth rates and led to out-competition. Media composition led some knockdowns to compete differentially as biofilm versus non-biofilm colonies. Cells dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
(81 reference statements)
6
15
0
Order By: Relevance
“…In contrast to these metabolites, alanine can not only be used as carbon source, but also as a nitrogen source in the cross-feeding-dependent region, and we note that it is currently not clear what limits growth in the higher regions of the colonywhether it is carbon, nitrogen, or other elements such as iron, sulfur, or phosphorous. Very recently, it was shown that alanine can be cross-fed in colonies of the Gram-positive bacterium Bacillus subtilis, and that this effect required three-dimensional colonies for unknown reasons (Arjes et al, 2021). In our E. coli model system, three-dimensional growth is required to create an anaerobic region replete with carbon and nitrogen sources that causes alanine secretion, and we speculate that this effect may also be required in B. subtilis, and in many other species.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast to these metabolites, alanine can not only be used as carbon source, but also as a nitrogen source in the cross-feeding-dependent region, and we note that it is currently not clear what limits growth in the higher regions of the colonywhether it is carbon, nitrogen, or other elements such as iron, sulfur, or phosphorous. Very recently, it was shown that alanine can be cross-fed in colonies of the Gram-positive bacterium Bacillus subtilis, and that this effect required three-dimensional colonies for unknown reasons (Arjes et al, 2021). In our E. coli model system, three-dimensional growth is required to create an anaerobic region replete with carbon and nitrogen sources that causes alanine secretion, and we speculate that this effect may also be required in B. subtilis, and in many other species.…”
Section: Discussionmentioning
confidence: 76%
“…Several cross-feeding interactions have been described in detail for multi-species communities (Henson et al, 2019;Kim et al, 2017;Moree et al, 2012;Pande et al, 2016;Røder et al, 2020;Smith et al, 2019;Watrous et al, 2013;Yang et al, 2009). Even though cross-feeding interactions are likely a ubiquitous process in single-species bacterial multicellular structures (San Roman & Wagner, 2018), only a few metabolic interactions between subpopulations have been documented for single-species biofilms (Arjes et al, 2021;Cole et al, 2015;Evans et al, 2020;Lin et al, 2018;Liu et al, 2015). For E. coli colonies grown on agar-solidified medium, and for bacterial communities in general, it is still unclear how many subpopulations interact metabolically, and on which length and time scales these interactions take place, and how significant these many interactions are for the community growth and stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical models on surface growth are paralleled by a large body of empirical literature where surface-associated organisms are studied by either growing collectives in isolation (e.g., biofilms, colonies, pellicles, swarms, fruiting bodies) [110][111][112][113], thereby focusing on their multicellular organization [36,[114][115][116][117][118], or by competing several genotypes against each other on a surface [30,[119][120][121][122][123][124]. Competition experiments revealed that spatial interactions can strongly affect the outcome of competition, oftentimes leading to the coexistence of multiple genotypes [43,120,125].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, during liquid growth after passaging BT2397 (tnr3) through a colony, we observed reversion to wild-type phenotypes, indicating that growth conditions can play a major role in B. theta phenotypes. In the future, it will be interesting to screen the condensed collection in diverse media conditions to uncover additional phenotypes, as a previous screen of a CRISPRi library of Bacillus subtilis essential-gene depletions uncovered a wider distribution of phenotypes in a minimal medium compared with LB (48).…”
Section: Discussionmentioning
confidence: 99%